Prevalence and predictors for low total testosterone levels among male type 2 diabetic patients: an Egyptian experience - Aboelnaga, Mohamed M.; Elshahawy, H. (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes mellitus (DM) affects an estimated 285 million people worldwide. This number is expected to reach 438 million by the year 2030. The aim of this study was to determine the prevalence of male hypogonadism among Egyptian patients with type 2 diabetes and to identify the risk factors may be associated with low serum testosterone concentrations in men with type 2 diabetes. Methods: 140 male patients with type 2 diabetes were recruited in this cross-sectional study. This study WAS conducted from January 2012 to January 2016 in the endocrinology and metabolism unit, Mansoura University, Egypt. Results: We found 48 (34.2%) patients with hypogonadism (defined as TT ≤300 ng/dl) among 140 male patients with type 2 diabetes. 7 out of 48 (14.5%) patients with TT ≤300 ng/dl had high abnormal gondotrophins hormones levels while 41 patients out of 48 (85.5%) had normal gondotrophins hormones levels. We found BMI, WC, Hba1c, UACR, retinopathy ratio, nephropathy ratio, smoker ratio and patient on insulin therapy ratio were increased in the low TT group with statistically significance, but non statistically significant difference in age, diabetic duration, FSH, LH, Prolactin and lipid profile. In this study by using Pearson correlation, we found a statistically significant correlation between TT levels with BMI, WC, FSH, LH, Hba1c, and UACR (P value<0.05). Also by using stepwise multiple regression analysis, we found BMI, WC, LH, Hba1c, and UACR were statistically significant predictors of TT levels. In logistic regression analysis, we found Hba1c, UACR, and WC were statistically significant risk factors for MHG. Conclusions: Visceral obesity, higher Hba1c, and degree of albuminuria are independent risk factors for hypogonadism in Egyptian male patients with type 2 diabetes.